Physicochemical and sensory traits of meat from Santa Inês lambs slaughtered with different subcutaneous fat thicknesses - Andrade,Ana Carla Santana (2015)
Physical (pH, color, tenderness, and cooking weight loss), chemical (moisture, crude protein, ash, and lipids) and sensory (odor, flavor, juiciness, and overall acceptance) characteristics of meat from Santa Inês lambs slaughtered with 2.0, 3.0, and 4.0 mm of subcutaneous fat thickness (SFT) were evaluated. Samples of the longissimus dorsi muscles were removed from 24 male uncastrated lambs distributed in a completely randomized design with three treatments and eight replicates. Weightings and ultrasound evaluations were performed every 14 days. No significant differences were observed for pH0h, which averaged 6.24. Lambs slaughtered with 4.0 mm SFT differed from the treatments with 2.0 and 3.0 mm as to the pH24h values. The meat from lambs slaughtered with 3.0 and 4.0 mm SFT showed a greater lightness (L*) value. Meat tenderness (2.21 kgf/cm2), cooking weight loss (13.90%), moisture (74.39%), and crude protein (22.10%) contents were not affected by the SFT. For the total lipid contents of the meat, significant differences were observed between the lambs slaughtered with 2.0 mm and those with 3.0 and 4.0 mm SFT. The sensory traits were not affected by the SFT with which the lambs were slaughtered. Lambs slaughtered with 4.0 mm SFT remained 33 days longer in feedlot and showed similar live weights at slaughter to those with 3.00 mm. It is recommended to slaughter Santa Inês lambs with a subcutaneous fat thickness of 3.00 mm.